THE EFFECT OF PROFITABILITY AND LEVERAGE ON TAX AVOIDANCE IN THE HEALTHCARE SECTOR FOR THE PERIOD OF 2020-2024 - Sri Widiyati; Wiralestari; Ilham Wahyudi; Enggar Diah Puspa Arum (Yayasan Nuraini Ibrahim Mandiri, 2026)
The purpose of this study is to examine how profitability and leverage affect tax evasion in healthcare firms that are listed on the Indonesia Stock Exchange between 2020 and 2024. Due to its potential to result in large losses in state income, tax avoidance has emerged as a critical concern, and businesses must effectively manage their capital structures and earnings. This study exerts a purposive sampling methodology in conjunction with a descriptive quantitative method, yielding 55 observational samples from 11 firms. Tax avoidance is measured by the Effective Tax Rate (ETR), profitability by Return on Assets (ROA), and leverage by the Debt to Equity Ratio (DER). SPSS version 23 was utilized to analyze the data using multiple linear regression. Profitability has a negative and substantial impact on tax evasion, according to the partial test findings (t-test) with a significance value of 0.003. This suggests that businesses with greater profit levels are more likely to comply with their tax duties to avoid fines. Leverage, on the other hand, has no discernible impact on tax evasion (sig. 0.556), suggesting that the healthcare industry uses debt more for operational funding than for tax-cutting measures. Both factors significantly influence tax evasion at the same time with an F-value of 5.599 (sig. 0.006) and a coefficient of determination of 17.7%. Regulators and investors can better understand business tax behavior in the healthcare industry thanks to this study.